2017
DOI: 10.1002/jnr.24059
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin axons in the neocortex of the adult female mouse regrow after traumatic brain injury

Abstract: It is widely held that injured neurons in the central nervous system do not undergo axonal regrowth. However, there is mounting evidence that serotonin axons are a notable exception. Serotonin axons undergo long-distance regrowth in the neocortex after amphetamine lesion and, following a penetrating stab injury, they can regrow from cut ends to traverse the stab rift. Traumatic brain injury (TBI) is clinically prevalent and can lead to pathologies such as depression that are related to serotonergic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Might the apparent loss and regrowth of TH+ axons following CCI, indicated by TH+ immunohistochemistry, be an artifact produced by nonspecific tissue damage? The observation that, at the one month postinjury time point, the tissue anterior to the CCI injury showed significantly reduced TH+ axon density (Figure 3) but not serotonin axon density (Kajstura et al, 2018), argues against a non-specific reduction in axonal immunopositive signals. Likewise, the failure of CCI injury to produce significant reductions in cholinergic axon density, indicated by VAChT immunohistochemistry, in any neocortical layer, either anterior or posterior to the CCI injury site (Figure 7 and Supplementary Figure 1) argues that the loss and recovery of TH+ axons seen here following CCI was a specific effect.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Might the apparent loss and regrowth of TH+ axons following CCI, indicated by TH+ immunohistochemistry, be an artifact produced by nonspecific tissue damage? The observation that, at the one month postinjury time point, the tissue anterior to the CCI injury showed significantly reduced TH+ axon density (Figure 3) but not serotonin axon density (Kajstura et al, 2018), argues against a non-specific reduction in axonal immunopositive signals. Likewise, the failure of CCI injury to produce significant reductions in cholinergic axon density, indicated by VAChT immunohistochemistry, in any neocortical layer, either anterior or posterior to the CCI injury site (Figure 7 and Supplementary Figure 1) argues that the loss and recovery of TH+ axons seen here following CCI was a specific effect.…”
Section: Discussionmentioning
confidence: 95%
“…Controlled Cortical Impact CCI injury was performed as previously described (Kajstura et al, 2018). Briefly, mice were anesthetized with 3% isoflurane and placed in a stereotaxic device (Stoelting) with continued isoflurane delivery.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…They begin synthesizing serotonin around embryonic day 11-13 in the mouse and rat brains (Lidov and Molliver, 1982;Hendricks et al, 1999;Hawthorne et al, 2010) and around 5 weeks of gestation in the human brain (Sundstrom et al, 1993;Mai and Ashwell, 2004). In the adult mammalian brain, serotonergic axons are unusual in their ability to regenerate, with potential implications for the efforts to restore other axon systems after injury (Hawthorne et al, 2011;Jin et al, 2016;Kajstura et al, 2018). A recent study has shown that they may share this property with other axons in the ascending reticular activating system (Dougherty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%